Predicting risk and prognosis of preeclampsia by evaluating platelet indices - Agarwal, Shaily; Gupta, Renu; Dwivedi, Divya; Kala, Chayanika; Singh, Mrinalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia is an obstetric disorder affecting 2-8% pregnancies globally and 8-10% pregnancies in India. The study was conducted to evaluate platelet count, mean platelet volume and platelet distribution width as potential predictor of preeclampsia. It also aimed to see if these platelet indices have a prognostic significance in determining the preeclampsia severity. Methods: A prospective study was conducted on 120 pregnant women at 20 to 24 weeks of gestation with singleton pregnancy. At monthly intervals CBC (complete blood count) was done from 20 to 24 weeks till delivery and 7 days after delivery. Data with increasing gestation were collected, analysed and expressed as mean, standard deviations and correlation coefficients. Results: We observed significant decrease in PC and increase in MPV and PDW in patients with preeclampsia compared to normotensive patients. We also observed that it was more significant in severe preeclampsia than non-severe preeclampsia. The r value of PC for normotensive, non-severe and severe preeclampsia was -0.58, -0.59 and -0.94 respectively. The r value of MPV for normotensive, non-severe and severe preeclampsia was 0.89, 0.97 and 0.98 respectively. The r value of PDW for normotensive, non-severe and severe preeclampsia was 0.98, 0.98 and 0.99 respectively. Conclusions: Patients with preeclampsia are more likely to have changes in PC, MPV and PDW, which can be observed in early pregnancy. Thus, estimation of PC, MPV and PDW can be considered as an early, simple and cost-effective procedure in the estimating the severity of preeclampsia